Calretinin Immunoreactivity in the VIIIth Nerve and Inner Ear Endorgans of Ranid Frogs - Reichenberger, Ingrid; Caussidier-Dechesne, Claude J.; Straka, Hans (Frontiers in Neuroscience, 2021)
Calcium-binding proteins are essential for buffering intracellular calcium concentrations, which are critical for regulating cellular processes involved in neuronal computations. One such calcium-binding protein, calretinin, is present in many neurons of the central nervous system as well as those which innervate cranial sensory organs, although often with differential distributions in adjacent cellular elements. Here, we determined the presence and distribution of calretinin-immunoreactivity in the peripheral vestibular and auditory system of ranid frogs. Calretinin-immunoreactivity was observed in ganglion cells innervating the basilar and amphibian papilla, and in a subpopulation of ganglion cells innervating the saccular epithelium. In contrast, none of the ganglion cells innervating the lagena, the utricle, or the three semicircular canals were calretinin-immunopositive, suggesting that this calcium-binding protein is a marker for auditory but not vestibular afferent fibers in the frog. The absence of calretinin in vestibular ganglion cells corresponds with the lack of type I hair cells in anamniote vertebrates, many of which in amniotes are contacted by the neurites of large, calyx-forming calretinin-immunopositive ganglion cells. In the sensory epithelia of all endorgans, the majority of hair cells were calretinin-immunopositive. Weakly calretinin-immunopositive hair cells were distributed in the intermediate region of the semicircular canal cristae, the central part of the saccular macula, the utricular and lagenar striola and the medial part of the amphibian papilla. The differential presence of calretinin in the frog vestibular and auditory sensory periphery might reflect a biochemical feature related to firing patterns and frequency bandwidths of self-motion versus acoustic stimulus encoding, respectively.